Sustaining and Revitalizing Oral Tradition Taur-Taur Simalungun Ethnic: An Ethnography Approach as a Preservation of Language and Cultural Values - Mandra Saragih; Pirman Ginting; Yenni Hasnah; M. Avif Toni S. Saragih (Institut Agama Islam Negeri Palopo, 2024)
This study discusses the Simalungun oral tradition, namely the Taur-taur Simalungun which began to be abandoned so that it was at the point of extinction because it was abandoned by some users of the oral tradition. One way to overcome this is to document the simalungun oral tradition. This research provides a solution to protect the oral tradition of the Taur-taur Simalungun from extinction. Taur-taur Simalungun is an oral tradition of the Simalungun community in the form of poetry and rhymes and contains stories, advice and satire. The aims of this study were (1) to describe the performance of the Taur-taur Simalungun oral tradition, (2) to evaluate the value content contained in the Taur-taur Simalungun oral tradition, and (3) to find a revitalization model for the Taur-taur Simalungun oral tradition. The Taur-taur Simalungun oral tradition that can be passed down from generation to generation.. The method used is an ethnographic method which includes in-depth interviews and participant observation. By conducting in-depth interviews and participatory observations, the pattern of using the Simalungun language itself will be obtained. Research data in the form of audio recordings, videos, interviews and observations. The results showed that through an anthropolinguistic approach as a whole (text, co-text and context), the oral tradition of the Taur-taur Simalungun can be maintained by documenting the oral tradition in audio-video form, in written format, as well as by developing local content subject matter at school.